2017
DOI: 10.1007/s40596-016-0655-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Knowledge and Behaviors in Medical Students: Results of a Single Center Survey

Abstract: Objective There is little known about the demands of medical school on students’ sleep behavior. The study’s main goal was to examine the interplay between medical students’ sleep knowledge, personal attitudes towards sleep, and their sleep habits. Methods An anonymous online survey was created and emailed to all students enrolled at a large metropolitan medical school. Data on demographics, sleep perception and habits in addition to self-reported measures of students sleep knowledge, beliefs and sleepiness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
0
22
1
4
Order By: Relevance
“…Clinical students had considerably more sleepiness than preclinical students and clinical students were also more knowledgeable about the topic of sleep. Preclinical and clinical students held similar views about sleep, as measured by the Dysfunctional Beliefs and Attitudes about Sleep (DBAS) scale [3]. This study also examined whether students used prescription sleep medication, over-the-counter sleeping pills, or behavioral sleep strategies.…”
Section: Sleep Behaviors Of Medical Studentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical students had considerably more sleepiness than preclinical students and clinical students were also more knowledgeable about the topic of sleep. Preclinical and clinical students held similar views about sleep, as measured by the Dysfunctional Beliefs and Attitudes about Sleep (DBAS) scale [3]. This study also examined whether students used prescription sleep medication, over-the-counter sleeping pills, or behavioral sleep strategies.…”
Section: Sleep Behaviors Of Medical Studentsmentioning
confidence: 99%
“…Ahmed et al [3] performed a cross-sectional study of medical students at SUNY Downstate Medical School (n = 261). The authors found that, on average, more than 70% of students felt they needed 7 h of sleep each night; however, only one quarter of students slept an average of 7 h nightly.…”
Section: Sleep Behaviors Of Medical Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these would lead to profound change of theory, practice and application of educational technology discipline (Joo et al, 2015). In China, distance education has been greatly developed in recent years (Ahmed, Sadat, Cukor, 2017). The Ministry of Education of China approved to allow 67 universities to develop pilot project of modern remote education, opening over 140 majors in 10 primary discipline fields (engineering, management, medicine, literature, science, agriculture, economics, pedagogy, law, philosophy), and constructing nearly 2,000 off-campus learning centers for modern distance education, with total webucation registration number of more than 1,600,000.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to implement the new standard, in the assessment of school scores, it should be in accordance with the overall review instead of overly concerned with some specific standards that school need to fulfill (Ahmed et al, 2017).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%